Price discrimination through cause‐related marketing. Issue 4 (5th May 2022) - Shankar, Kameshwari; Ghosh, Suman
Abstract: A common form of Corporate Social Responsibility (CSR) by firms is to agree to donate a fixed portion of private good revenues to a charitable cause. In this paper, we explore a new rationale for such CSR known commonly as Cause‐Related Marketing (CRM). We argue that linking private good purchase with charitable donations to a partnering nongovernmental organization (NGO) allows the firm to price discriminate between altruistic consumers who wish to make charitable donations out of their income and nonaltruistic consumers who do not place any value on such donations. The disparity in altruistic propensities translates into a difference in private good value which limits the firm's ability to extract consumer surplus in the private good market. Linking private good sales to charity brings down the variation in private good value and enables the firm to appropriate greater surplus. At the same time, by inducing nonaltruistic consumers to donate through their purchase of the charity‐linked good, CRM may also increase charitable donations to the NGO beyond the level that would be achieved under the standard voluntary contributions equilibrium. We extend our model to consider the effects of CRM on profits and donations when altruistic consumers can choose between donating directly to the NGO out of their income and donating through their purchase of the charity‐linked good. We consider this choice in the context of CRM advertising where firms make the altruism of their consumers public and thus provide exhibition value to donations made through the charity‐linked good. We find that the case for CRM strengthens when we allow the firm to appropriate exhibition utility through advertising while enabling greater donations for the NGO through direct donations as well as CRM.